Potential duration of unemployment benefits and labor market outcomes for older workers with health impairments in Germany - Inna Petrunyk; Christian Pfeifer (Bulletin of Economic Research, 2022)
This research note estimates the causal effects of a cut in the potential duration of regular unemployment benefits for older workers in Germany on the labor market outcomes of individuals with health impairments. The analyzed reform is a natural experiment that allows a difference-in-differences strategy with treatment intensity. The results provide evidence for a significant decrease in the number of days in regular unemployment benefits and an increase in the number of days in employment. However, the results also suggest a significant increase in the number of days in unemployment (social) assistance, which are granted upon exhaustion of regular unemployment benefits.
Keywords: 330; difference-in-differences; labor market reform; policy evaluation; unemployment insurance